Nanowire formation using electron beam lithography - Rahman, S. F. A.; Uda, Hashim, Prof. Dr.; Mohammad Nuzaihan, Md Nor; Mohamed Nuri, A. M.; Mohamad Emi Azri, Shohini; Salleh, S. (American Institute of Physics, 2010)
Link to publisher's homepage at http://www.aip.org/